Devoicing of Polish sibilant fricatives: the case of a speaker from Gdynia - Jiménez Bernales, Renzo Adrián (2022)
In the present study, we analyze the devoicing of the sibilants /z/, /ʑ/ and /ʐ/ of a native speaker of Polish from the town of Gdynia. In the phonological analysis, we followed the linear model, proposed by Chomsky and Halle (1968), and the hierarchical autosegmental model of Nuñez-Cedeño (2014), both belonging to generative phonology. The results show that the devoicing of alveolar, alveopalatal and retroflex sibilants occurs in a) implosive position, followed by a voiceless obstruent, and b) at the end of the word. Likewise, the process of devoicing of the retroflex sibilant /ʐ/ was found when it is preceded by a voiceless occlusive. On the other hand, the analysis reports a condition in which the sequence of final voiced sibilant followed by a voiced occlusive would be necessary for sonority preservation. Finally, the observed processes are explained by the formulation of three phonological rules.